Evaluation of a patient education manual. Issue 6245 (4th October 1980) - Anderson, J E; Morrell, D C; Avery, A J; Watkins, C J
Abstract : A randomised controlled trial has shown that introducing a health education booklet describing the management of six common symptoms resulted in fewer consultations for the symptoms described by families receiving this booklet compared with a control group. A sample of the mothers in each group was subsequently followed up by an interview, at which a questionnaire was administered. This was designed to measure the mother's knowledge of the management of the symptoms described. The booklet did not lead to any increase in knowledge in the mothers receiving it. The questionnaire did, however, show that 76% of the mother had consulted the booklet at some time in the year of the study and 28% had consulted it in the three months before interview. The important result was a fall in the new request for care for the symptoms described in the booklet. This may be interpreted as indicating that what patients need to respond appropriately to common symptoms of illness is a simple reference manual rather than an educational programme designed to increase their knowledge about the management of illness.